LANDASAN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Aulia, Mizar (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
The curriculum occupies a strategic position in the implementation of education, because it is a plan and guide for teaching and learning activities. The importance of the curriculum requires seriousness in the preparation process. The preparation and development of the curriculum must be based on strong foundations so that the curriculum is formed directed and systematic. This study examines the nature of the foundation of curriculum development, types and design of curriculum development. The purpose of this study is to examine and describe the nature of the foundation of curriculum development, explain the various foundations of curriculum development and curriculum development design. The research method used in writing this article is a literature study. The results of this study found that the nature of the foundation of curriculum development is the things that must be considered in preparing the curriculum. The foundation of the curriculum consists of a philosophical foundation, a psychological foundation, a sociological foundation and a foundation of science and technology. Applying the main foundations in the preparation and development of the curriculum will form an effective and efficient curriculum that helps achieve the planned educational goals.